Sintering effect on mechanical properties of composites of natural hydroxyapatites and titanium - Salman, S.; Gunduz, O.; Yimaz, S.; Ovecoglu, M. L.; Snyder, R. L.; Agathopoulos, S.; Oktar, F. N. (Elsevier BV, 2009)
Abstract This study presents the fabrication and characterization of composite materials of hydroxyapatite and Ti. Hydroxyapatite (HA) powder was obtained from bovine bones (BHA) and human enamel (EHA) via calcination technique. Fine powders of HA were admixed with 5 and 10 wt.% fine powder of metallic Ti. Powder-compacts were sintered at different temperatures between 1000 and 1300 °C. Compression strength, Vickers microhardness and elastic modulus as well as density were measured. SEM and X-ray diffraction studies were also conducted. The experimental results showed that addition of Ti to EHA and BHA decreases the elastic modulus, comparing to samples of pure BHA. The best mechanical properties for BHA–Ti composites were obtained after sintering in the range of 1200–1300 °C and for EHA–Ti composites in the range of 1100–1300 °C.
Keywords: sintering; microstructure; hydroxyapatite; temperature; titanium; coatings; mechanical properties